Analysis of the requirements of the EU strategic framework on safety and health at work - Golovnya, Diana; Yevtushenko, Olga; Siryk, Alina; Litvynchuk (Vorontsova), Svitlana (My University, 2025)
Дослідження було проведено на основі аналізу Стратегічної рамкової програми ЄС з безпеки та гігієни праці на 2021-2027. Встановлено, що підтримка та вдосконалення стандартів захисту працівників на основі Стратегічних рамок ЄС є нагальною потребою, враховуючи, що Україна рухається до Європейського Союзу. Процес досягнення трьох цілей програми базується на: соціальному діалозі; зміцненні доказової бази; посиленні правоохоронної діяльності; підвищенні обізнаності; та фінансуванні. Це дозволяє сформулювати оновлену модель системи управління охороною праці з точки зору зменшення втрат здоров'я та життя працівників

The study was conducted based on the analysis of the EU Strategic Framework Programme on Safety and Health at Work for 2021-2027. It has been established that maintaining and improving worker protection standards based on the EU Strategic Framework is an urgent need, given that Ukraine is moving towards the European Union. The process of achieving the three objectives of the programme is based on: social dialogue; strengthening the evidence base; strengthening law enforcement; raising awareness; and financing. This allows for the formulation of an updated model of the occupational safety and health management system from the point of view of reducing losses of health and life of workers
Keywords: кафедра фізики та професійної безпеки; професійне захворювання; гігієна праці; нещасний випадок; occupational disease; occupational hygiene; accident